Union sacrée 1914 - Rosmer, Alfred; Modiano, Hélène; Martinet, Marcel ([Paris] : J. Lefeuvre, 1948)
Bibliotheek François Vercammen
Frans
Brochure
Keywords: Tweede Internationale (1889-1919).; Wereldoorlog 1